INSTRUCTIONAL DESIGN ON MOBILE LEARNING - ชื่นสมบัติ สืบวงศ์; มณีนิล สิริกัญญา (ECT Education and Communication Technology Journal, 2020)
Mobile Learning or learning management via mobile devices has an important feature which is learning that occurs at any time and anywhere, according to the convenience of students via mobile devices. The learning activities can be combined both face to face and online effectively in the form of interaction and collaboration. Mobile learning can occur by using technology and tools on mobile devices, which is fast in data communication through wireless network technology with security and privacy to access information of each student. It can be seen that mobile learning is related to both education management and information technology, which are intermediaries in learning management. Therefore, learning can be effective and efficiency must go through the systematic design process for teaching and learning. Thus, this article synthesizes the whole knowledge of educational teaching design and information technology design into 5 steps of the teaching system design on mobile learning, consisting of 1) Learning Situation Analysis 2) Learning Experience Design 3) Learner Interface Design 4) Creation and Testing and 5) Implementation, Evaluation, and Improvement